Thermal Experimental Dielectric Characterization of Cost-Fewer Low-Density Polyethylene Nanocomposites - Osama Gouda; Ahmed Thabet Mohamed (Advances in Electrical and Electronic Engineering, 2014)
Polymer properties can be experimentally tailored by adding small amounts of different fillers, but they are expensive with respect to the classical polymer materials. This paper has been studied the enhancement and controlling of electric and dielectric properties of low-density polyethylene (LDPE) polymer materials by cost-fewer nanoparticles. Certain percentages of clay and fumed silica nanoparticles have been enhanced electric and dielectric properties of low-density polyethylene nanocomposite. Dielectric spectroscopy has been measured the electric and dielectric properties of low-density polyethylene with and without nanofillers at various frequencies (10Hz-100kHz) and temperatures (20°C, 40°C and 60°C). Also, it has been investigated the optimum percentages of nanofillers with respect to nanofillers type, filler concentration and temperature for enhancing electric and dielectric characterization of low-density polyethylene. Experimental measurements have been carried out on dielectric breakdown strength of new polyethylene nanocomposites materials under variant electric fields (uniform, and non-uniform) and variant temperatures. It has been specified the effective nanofillers factors on dielectric breakdown strength of polyethylene nanocomposites materials.